Tecnologias de informação e comunicação para analisar a responsividade emocional em organizações hierárquicas - Silva, Rener Baffa da (2016)
Currently the area of HCI is experiencing the years of its third paradigm or third wave where the cultural issues and specially the human expressions such as emotions are very important. It is part of the human nature the need to express emotions, which play an important role in the development of intelligence, perception, learning and specially in communication. Given that people organize themselves in group in different situations, mainly for work purposes, the importance of communication is clear within these organizations that are mostly hierarchically organized. The communication that occurs without expression of emotions and understanding and response of the emotions expressed by other take the risk of loose sense. Thus, it is clear that emotions and emotional responsiveness are present in the communication and socialization among people. However, little is known about the "emotional world" of hierarchical organizations. This work explores the use of ICTs tools in the context of the communication in hierarchical organizations to look for emotional responsiveness and behavioral tendencies of their members. For this end, a prototype named EmotiFeed was developed and installed in a hierarchically organized mental care hospital, following the in-the-wild approach. The EmotiFeed encourages the Bottom-Up communication and allows the hospital directors to publish public notes to their employees that can express themselves emotionally about them. It was found evidences that the emotional responsiveness is promoted by the use of ICTs from both perspectives of high-level and low-level members. It was found that the high-level members are sensitive to the emotional feedback provided by the low-level members, checking and evaluating the impact of his/her publication and adjusting the content of the public notes, tending to publish public notes with emotional content above neutral and around positive. It was also found that the low- level members have sensitivity to the repost of the high-level members, reflecting on the previous and the current public note and can be expressed in order to be better understood.